Transformasi Akuntabilitas PFM Era Danantara: Sebuah Tinjauan Sistematis - Alam, Arya Pamungkas Pitu; Rina Tjandrakirana DP (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study examines whether the evolution of public financial management reflects a paradigm shift from budget accountability to portfolio accountability in the era of sovereign wealth governance, particularly in the context of Danantara. Using a qualitative systematic literature review, the study synthesizes recent research on public financial management, performance-based budgeting, accrual accounting, public asset management, and sovereign wealth fund governance. The findings indicate that portfolio accountability does not yet represent a fully established paradigm shift but rather a conceptual expansion of performance-based governance. While traditional accountability emphasized compliance, annual budget execution, and ex-post audit control, emerging practices increasingly incorporate risk-adjusted return, asset valuation, financial sustainability, and portfolio-level risk management. Epistemically, positioning government as a portfolio manager balancing risk, public value, and intergenerational sustainability signals the potential emergence of a new governance sub-paradigm. This study contributes by integrating fragmented discourses into a unified analytical framework and proposing portfolio accountability as a conceptual lens for evaluating contemporary fiscal governance transformation.